Search for CP violation in the decay D+→π−π+π+ - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Hansmann-Menzemer, Stephanie; Jäger, Andreas; Kreplin, Katharina; et al. (Physics letters, 2014)
A search for CP violation in the phase space of the decay D+→π−π+π+ is reported using pp collision data, corresponding to an integrated luminosity of 1.0 fb−1, collected by the LHCb experiment at a centre-of-mass energy of 7 TeV. The Dalitz plot distributions for 3.1×106 D+ and D− candidates are compared with binned and unbinned model-independent techniques. No evidence for CP violation is found.